Ultrasonography of the peri‐ and intraventricular areas of the fetal brain between 26 and 36 weeks' gestational age; a comparison with neonatal ultrasound - van Gelder‐Hasker, M. R.; van Wezel‐Meijler, G.; van Geijn, H. P.; De Vries, J. I. P. (Ultrasound in obstetrics & gynecology, 2001)
Objectives To determine to what extent the peri‐ and intraventricular areas of the fetal brain can be visualized in coronal and sagittal planes using high‐frequency transvaginal ultrasound. Design In a longitudinal study, fetuses of 30 low‐risk pregnancies were studied at 26, 28, 30, 32, 34 and 36 weeks' gestational age. The neonates were examined within the first week of life. Visualization of the peri‐ and intraventricular areas was systematically scored in six coronal and five sagittal planes. The degree of echogenicity of the periventricular area was assessed. Inter‐ and intra‐observer agreements were calculated. Results For fetuses in the cephalic position, the highest percentages of visualization of the planes were obtained between 26 and 32 weeks' gestational age (>70% in four coronal and three sagittal planes). Transient periventricular echodensities were observed at 26 and 28 weeks' gestational age in 6/39 observations in the cephalic position. Small choroid plexus cysts were found in three fetuses with the changes persisting in two until after birth. Seven neonates developed mild periventricular echodensities/translucencies not present during fetal development. The mean interobserver agreement was 0.77 (95% confidence interval (CI) 0.73–0.81). The intra‐observer agreement varied between 0.48 and 0.72 (mean 0.6, 95% CI 0.47–0.75). Conclusions Transvaginal ultrasonography can be applied as a diagnostic tool to evaluate the peri‐ and intraventricular areas of the fetal brain. Transient periventricular densities can be encountered between 26 and 28 weeks. Term low‐risk neonates may develop transient periventricular densities or translucencies. Copyright © 2001 International Society of Ultrasound in Obstetrics and Gynecology